The epidemiology and diagnosis of childhood tuberculosis at a district hospital in Kwazulu-Natal, South Africa : a retrospective audit of clinical practice - Padayachee, Samantha (Department of Paediatrics and Child Health, 2015)
Includes bibliographical references.